2017
DOI: 10.1097/ede.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Variable Analyses and Selection Bias

Abstract: Instrumental variables (IV) are used to draw causal conclusions about the effect of exposure E on outcome Y in the presence of unmeasured confounders. IV assumptions have been well described: 1) IV affects E; 2) IV affects Y only through E; 3) IV shares no common cause with Y. Even when these assumptions are met, biased effect estimates can result if selection bias allows a non-causal path from E to Y. We demonstrate the presence of bias in IV analyses on a sample from a simulated dataset, where selection into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…However, the full practical implications for MR estimates of a time lag between randomization at conception and study recruitment often in late adulthood [14] have not been fully considered. Although several scenarios relevant to selection bias have been addressed, such as selective survival on exposure [15,16], on exposure and outcome [17], on exposure and other causes of the outcome [18][19][20] or on instrument and other causes of the outcome [12,19], i.e. competing risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the full practical implications for MR estimates of a time lag between randomization at conception and study recruitment often in late adulthood [14] have not been fully considered. Although several scenarios relevant to selection bias have been addressed, such as selective survival on exposure [15,16], on exposure and outcome [17], on exposure and other causes of the outcome [18][19][20] or on instrument and other causes of the outcome [12,19], i.e. competing risk.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 1d and 1e show survival on both instrument and common causes of the outcome (U2) [12,19]. The time lag between randomization (at conception) and typical recruitment into genetic studies of major diseases in middle-to old-age means some MR studies may inevitably recruit on surviving both the genetic [11,13,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the results of our simulation study, non-trivial levels of selection bias were demonstrated via simulations [24,23,22,19,21,18]. [18] investigated two selection mechanisms in the context of Mendelian randomisation, and the remaining papers only considered a specific selection scenario.…”
Section: Discussionmentioning
confidence: 72%
“…Although selection bias is understood in the methodological literature (e.g., [6,12,5]), it is seldom acknowledged in IV analyses or discussed in guidelines for IV analysis (e.g., [13,14,15,16,17]). However, recent exceptions include examples where selection depends on the: exposure plus confounder, or outcome [18], exposure [19,18], instrument plus measured and unmeasured confounders (of the outcome-exposure association) [20], exposure and measured variable (which causes the outcome) [21], missing values of measured covariates [22,23], and unmeasured confounder plus measured covariates [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation